Socio-technical futures and the governance of innovation processes—An introduction to the special issue - Konrad, Kornelia; Böhle, Knud (Futures : the journal of policy, planning and futures studies, 2019)
•Editorial Introduction to special issue on Socio-technical futures and the governance of innovation processes.•Twelve contributions draw on several lines of research mobilizing concepts developed in science and technology studies.•Examines how socio-technical futures are constituted, change and unfold over time•Shows how different socio-technical futures shape the governance of innovations and the actual technologies and systems.•Examines how forms of deliberative and reflective future-making can be integrated into policy and innovation processes. This special issue analyses and reflects on socio-technical futures as core elements in innovation processes and their governance. The special issue assembles twelve contributions that draw on several lines of research mobilizing concepts developed in science and technology studies, such as socio-technical imaginaries and the sociology of expectations, and technology assessment. The papers examine how socio-technical futures are constituted, change and unfold over time, shaped by different practices and in different contexts. Furthermore, they study how different socio-technical futures circulate amongst policy actors and others involved in the governance of innovations, how they shape the governance of innovations and the actual technologies and systems, and how forms of deliberative and reflective future-making can be integrated into policy and innovation processes.